Maximizing binding capacity for protein A chromatography. (2nd September 2014) - Ghose, Sanchayita; Zhang, Jennifer; Conley, Lynn; Caple, Ryan; Williams, Kevin P.; Cecchini, Douglas
<x xml:space="preserve">Abstract</x> Advances in cell culture expression levels in the last two decades have resulted in monoclonal antibody titers of ≥10 g/L to be purified downstream. A high capacity capture step is crucial to prevent purification from being the bottleneck in the manufacturing process. Despite its high cost and other disadvantages, Protein A chromatography still remains the optimal choice for antibody capture due to the excellent selectivity provided by this step. A dual flow loading strategy was used in conjunction with a new generation high capacity Protein A resin to maximize binding capacity without significantly increasing processing time. Optimum conditions were established using a simple empirical Design of Experiment (DOE) based model and verified with a wide panel of antibodies. Dynamic binding capacities of >65 g/L could be achieved under these new conditions, significantly higher by more than one and half times the values that have been typically achieved with Protein A in the past. Furthermore, comparable process performance and product quality was demonstrated for the Protein A step at the increased loading. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1335–1340, 2014